Proceedings of International Oil &Amp; Gas Conference and Exhibition in China 2006
DOI: 10.2523/103779-ms
|View full text |Cite
|
Sign up to set email alerts
|

Single-Trip, Multiple-Zone Frac Packing Offshore Sand Control: Overview of 58 Case Histories

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractIndustry experience has shown that frac pack completions can provide effective production stimulation and reliable sand control for unconsolidated sand reservoirs. One of the more rewarding areas of opportunity is in the completion of longer and more complex intervals that can be stimulated with a single frac pack, high-rate water-pack (HRWP) or EX-Tension Pac SM Service treatment. One of the major considerations in planning the \well completions in the BZ-25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Special fracturing treatment combined with gravel packing can produce highly conductive fractures to support cracks that can control grain migration, maximize sand placement, and assist steady gas flow . Industrial cases have shown that frac‐packing operations can reliably address both the sand‐control problem and provide effective production stimulation for unconsolidated reservoirs . According to Hainey and Troncoso, fracturing tests were conducted for two wells (A10 and D9) which were unable to produce prior to the treatment in the South Pass Block 61 Field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Special fracturing treatment combined with gravel packing can produce highly conductive fractures to support cracks that can control grain migration, maximize sand placement, and assist steady gas flow . Industrial cases have shown that frac‐packing operations can reliably address both the sand‐control problem and provide effective production stimulation for unconsolidated reservoirs . According to Hainey and Troncoso, fracturing tests were conducted for two wells (A10 and D9) which were unable to produce prior to the treatment in the South Pass Block 61 Field.…”
Section: Introductionmentioning
confidence: 99%
“…The use of larger gravel packs had contributed to better control of sand production. Liu et al presented frac‐pack design treatments in the offshore Bohai field in China. The production data showed sustained oil production of above 50BPD in multiple wells and all wells were produced with no sand.…”
Section: Introductionmentioning
confidence: 99%